2020
DOI: 10.2169/internalmedicine.4505-20
|View full text |Cite
|
Sign up to set email alerts
|

The First Case Report of Acute Symptomatic HEV Genotype 4 Infection in an HIV-positive Patient in Japan

Abstract: Hepatitis E virus (HEV) is a common cause of acute hepatitis. Four major genotypes of HEV have been studied, with genotype 4 being the predominant genotype across Asia. We herein describe the case of a 50year-old man with a history of human immunodeficiency virus (HIV) infection who was admitted with acute transaminitis. Serum anti-HEV-IgA and HEV-RNA were detected at the time of presentation and further testing revealed HEV genotype 4. To the best of our knowledge, this represents the first clinical case repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…1 ). This is consistent with clinical observations that both GT3 and GT4 HEV patients have been reported from these regions [ [13] , [14] , [15] , [16] ]. Although Europe is dominated by GT3, GT4 HEV has been identified in some peculiar cases including chronically infected patients [ 17 ].…”
Section: Resultssupporting
confidence: 92%
“…1 ). This is consistent with clinical observations that both GT3 and GT4 HEV patients have been reported from these regions [ [13] , [14] , [15] , [16] ]. Although Europe is dominated by GT3, GT4 HEV has been identified in some peculiar cases including chronically infected patients [ 17 ].…”
Section: Resultssupporting
confidence: 92%
“…Genotype III is distributed throughout the world, genotype IV is mainly distributed in Asia (Cossaboom et al., 2012 ; Miyashita et al., 2012 ), and genotypes III and IV can infect humans and are spread by many animals. The first clinical case of acute symptomatic HEV genotype 4 infection was reported in a patient in Japan in 2020 (Kitaura et al., 2020 ). Studies have found that in addition to humans, the hosts of HEV genotypes III and IV include macaques, chimpanzees, rhesus monkeys, pigs, deer, dogs, cattle, sheep, chickens, rabbits, bats and zigzags (Cossaboom et al., 2012 ; Meng, 2013 ; Pavio, et al., 2010 ; Saad et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-positive patient in Japan. 216 At present, the risk factors for HEV infection among HIV-positive patients are unknown. Several reports from France, [217][218][219] Belgium, 220 Italy, 221,222 the Netherlands, 223 Taiwan, 224 and Spain 225 have demonstrated that HEV endemicity remains low among HIV-positive patients, and that sexual transmission does not seem to be a main route of HEV infection in MSM, unlike HAV.…”
Section: Kitaura Et Al Reported Acute Symptomatic Hev-4 Infection In Anmentioning
confidence: 99%
“…Kitaura et al. reported acute symptomatic HEV‐4 infection in an HIV‐positive patient in Japan 216 . At present, the risk factors for HEV infection among HIV‐positive patients are unknown.…”
Section: Other Factorsmentioning
confidence: 99%